REAL-WORLD BURDEN OF CARDIORENAL COMPLICATIONS IN INDIVIDUALS WITH T2D IN MALAYSIA – EVIDENCE FROM ‘TAKE CARE OF ME’ REGISTRY - Subramaniam, Sudhakar; Jih, Yeo Tai; Velmunigan, Thinesh; Ahmad, Azura (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The burden of T2D and its cardiorenal complications (CRCs) are increasing in Malaysia with emerging evidence demonstrating high prevalence of asymptomatic cardiac dysfunction. In addition, there is an increasing incidence of dialysis initiation in the T2D population. The Take CaRe of Me programme, a subset of iCaReMe registry, aims to address the burden of silent CRCs by examining individuals with T2D from six low-to-middle income countries including Malaysia. METHODOLOGY This ongoing, prospective, real-world, observational registry is focused on evaluating diagnostic and management strategies for CRCs in T2D during routine care. Adults (≥18 years) with no known CRCs at index visit were enrolled in the study. Data extracted from medical records on clinicodemographic and treatment patterns are captured on cloud-based platforms. We present a descriptive analysis of the baseline characteristics of the Malaysia cohort. RESULTS Overall, 261 individuals (mean [SD] age 52.5 [14.0] years; 55.9% males; mean BMI 28.4 [7.6] kg/m2) were recruited. Mean duration of T2D was 13.7 (13.9) years with 44.7% having T2D duration greater than 10 years. Mean HbA1c was 6.7% (1.7%) with 70.1% under control (HbA1c <7%). Mean total cholesterol, LDLc, HDLc and triglycerides were 4.6 (1.2) mmol/L, 2.5 (1.1) mmol/L, 1.3 (0.4) mmol/L and 2.1 (1.1) mmol/L, respectively. As per ESC 2019 risk stratification, 32.6% individuals had very high/high CV risk. Of the individuals screened for renal risk using urine albumin-creatinine ratio (UACR) (N=207), 26.6% were categorized as A2 (UACR 30-300 mg/g) and 4.3% as A3 (UACR >300 mg/g). CONCLUSION There is high prevalence of undiagnosed CRCs in T2D patients with more than 30% having very high/high CV and renal risk. This emphasizes the need for early screening for CRCs to identify the at-risk population along with appropriate management of these patients with cardio- and renoprotective glucose-lowering agents.